The Epistemology of Land in an Adat Perspective: Philosophical Aspects of Human Relations With Land in the View of Mohammad Koesnoe - Moechthar, Oemar; Sekarmadji, Agus; Soelistyowati; Poespasari, Ellyne Dwi; Sampe, John Roberto (Media Iuris, 2024)
AbstractThe spirit of agrarian law reform in Indonesia has been proposed since 2001, but to date it has not been realized. On the one hand, the existence of adat law as the basis for the formation of national agrarian law as stated in the UUPA needs to be questioned again, whether it actually uses adat law as its raw material, or whether it still uses colonial law. The discussion in this article aims to contribute ideas related to the reform of agrarian law in Indonesia which is based on customary law regarding land. The direction of this reform is based more on the views of adat law expert, Mohammad Koesnoe. The type of research in this article is legal research using a conceptual approach and also a statute approach, and analyzed using historical, systematic and grammatical interpretation methods. The research results show that customary law is still relevant to use as a basis for legal reform in Indonesia while still referring to the rechtsidee of the Indonesian nation as stated in Pancasila. Therefore, agrarian reform in Indonesia should refer to the original law of the Indonesian people, namely adat law.Keywords: Adat Land Law; Agrarian Law Reform; Soil Epistemology.